STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN KESADARAN ETIKA DIGITAL SISWA DI ERA MEDIA SOSIAL - Fitriah; Maulidah Nafisah; Ansori (Makkah: Journal Of Islamic Studies, 2026)
: The rapid development of information technology and social media has brought significant changes to students' behavior and communication patterns. While social media provides various educational benefits, it also presents challenges such as cyberbullying, the spread of hoaxes, hate speech, and declining ethical awareness in digital interactions. Therefore, teachers, particularly Islamic Religious Education (PAI) teachers, play an important role in fostering students’ digital ethics awareness based on Islamic values. This study aims to analyze the strategies employed by PAI teachers in instilling digital ethical awareness among students in the era of social media. The research uses a qualitative approach with a library research method by examining various scientific articles, books, and relevant documents related to digital ethics, character education, and Islamic education. The findings indicate that PAI teachers can develop students’ digital ethical awareness through value internalization, exemplary behavior, habituation, digital literacy integration, and supervision of students’ online activities. Islamic values such as honesty, responsibility, courtesy, tolerance, and tabayyun serve as the primary foundation in shaping ethical digital behavior. The study concludes that strengthening digital ethics through Islamic education contributes significantly to students’ character formation and prepares them to become responsible digital citizens. The novelty of this study lies in integrating Islamic educational values with digital ethics education as a strategic framework for addressing contemporary challenges in students’ social media use.